Organizational Culture Transformation in Corrections Through a Management Psychology Approach: A Systematic Literature Review - Achmad Robbi (Polteknik Pengayoman Indonesia, 2025)
Organizational culture transformation within correctional institutions is a critical prerequisite for the success of rehabilitation programs and institutional reform. This study aims to examine the contribution of psychological management approaches to organizational culture change in correctional settings through a Systematic Literature Review (SLR). A total of 25 peer-reviewed articles published between 2013 and 2025 were analyzed. The findings reveal three main contributions of psychological management: (1) psychological empowerment that fosters motivation and work engagement; (2) transformational leadership as a driver of organizational value change; and (3) the creation of psychologically safe work environments as the foundation for inclusive culture. These factors collectively contribute to shifting organizational culture from authoritarian models toward more humanistic and adaptive frameworks. This study offers policy implications for psychosocially-informed institutional management and strategic managerial interventions in Indonesia’s correctional system.